Myostatin Serum Related with Sarcopenia Among Elderly Population - Ronald Winardi Kartika (Faculty of Medicine Universitas Kristen Duta Wacana, 2022)
BackgroundÂ Sarcopenia is a decrease in muscle mass accompanied by a decrease in muscle strength and performance. Sarcopenia arises from a disturbance of the complex balance between anabolic and catabolic factors. Myostatin strongly influences the inhibition of muscle growth by increasing muscle catabolism. Increased myostatin will atrophy in skeletal muscle. In the aging process, there will be an increase in the hormone myostatin plays an active role in the process of sarcopenia. The cause of the increase in myostatin hormone is a chronic inflammatory process that occurs in the aging process.Methods The writing of this paper is a literature review of the role of myostatin in sarcopenia that occurs due to the aging process.Results The incidence of sarcopenia in the elderly was 45 people (64.3%). The results of the analysis were a significant difference between myostatin levels in sarcopenia (47.59 ng/mL) and non-sarcopenia (39.7 ng/mL) subjects. The limit of myostatin levels that can cause an increase in muscle catabolic processes is 48.91 ng/mL. The prevalence ratio of the incidence of sarcopenia based on myostatin levels in the elderly was 3.84, while based on the combined risk of age and myostatin levels was 9.75.Conclusion From the literature review, it was found that there was a significant difference in myostatin levels between the elderly with and without sarcopenia. The prevalence of high myostatin levels in the elderly is almost 4 times higher than in young adults. This will lead to the progression of sarcopenia.